Effectiveness of Rodenticide Use in Controlling Rat Pest Attacks at PT. Maju Kalimantan Hadapan - Humairo Aziza; Edo Wijaya Kusuma; Fahrizal; Sri Ngapiyatun; Ahmad Zamroni (Jurusan Pertanian Politeknik Pertanian Negeri Samarinda Kampus Sei Keledang Jalan Samratulangi, Kotak Pos 192 Samarinda 75123, 2025)
Rat pests in oil palm plantations are the main problem causing losses in oil palm production. Therefore, one way that can be done is by chemical control using rodenticides. This study aims to determine the working mechanism and effectiveness of rat pest control using rodenticides in oil palm plantations. Observations were made for 22 days on the block which based on the census results has stated that the rate of basic attacks attacked by rat pests exceeds the economic threshold limit of 5%. The data collected were in the form of the number of observed trees and the subjects attacked by rat pests, the number of poisons used and calculated the percentage of attacks and the decrease in the percentage of attacks. The results of the study show that PT. Maju Kalimantan Ahead is making efforts to control the rat pest population chemically using chlorine poison which has rodenticide active substances. Regarding the effectiveness of the control techniques used, during the 22 days of observation with the number of Klerat poisons applied as many as 3,899 grains and 804 poisons consumed, there has been a decrease in the percentage of rat pest attacks which was originally at 19.82% (medium category) down to 2.40% (free category), or there has been a decrease in attacks by 87.89%. This indicates that the method carried out chemically using chloride poison with rodenticide content is very effective in controlling the spread of rat pest populations in oil palm plantations.